Parenting education toolkit working wi th families to support young children (New York : The World Bank/UNICEF)
This CD ROM presents strategies for strengthening families' competen cies to ensure thier young children's rights to survival, development, protection and participation, and has examples of programmes from over 30 countries. Good parenting programmes not only provide families with critical information on care practices, but they also help families dev elop skills and confidence in thier ability to give thier children the best in life.
Cover photo by Walter Silver
Keywords: Early childhood education